Transformasi Loro Blonyo – Rumah Joglo dalam Analisis Struktural - Slamet Subiyantoro (Humaniora, 2010)
This paper shows that the form and structure of a traditional Javanese house joglo is a transformation from loro blonyo sculptures representing a pair of human figures. This pair of statues and also the traditional Javanese house are basically a manifestation of the Javanese way of life that emphasizes harmony and unity of values between two different worlds such as men and women, physical and spiritual, and macrocosm and microcosm.